EVALUATION OF THE USAGE OF FINGERPRINT SYSTEM USAGE ON INMATES RESIDENTIAL ROOM'S INSPECTION OF SIDOARJO CLASS IIA PRISON INSTITUTION - Akbar, Raynaldi Cesar; Yuska, Syahrial (Universitas Nusa Cendana, 2025)
This study aims to evaluate the effectiveness of using the fingerprint system for residential room roll call in the Prisoner Block at the Class IIA Sidoharjo Penitentiary, which is designed to improve the security of the prisoner block, avoid head swapping between prisoners, and assist officers in accelerating the implementation of the inmate roll call. This study uses a qualitative method with an observation approach, document study, and in-depth interviews with the head of the prison security unit, head of the security squad, prison security unit staff, members of the guard squad, and two prisoners. The results of this study indicate that the fingerprint system is generally effective in identifying prisoners and accelerating the implementation of the residential room roll call. The time required for the residential room roll call was significantly reduced, and the incidents of illegal room transfers decreased. However, there are still some technical obstacles that cause identification failures and a lack of machines, so that use is still uneven. In addition, this system is considered less responsive to the increase in the number of prisoners and still requires routine maintenance. From an innovation perspective, the fingerprint system was well received by officers and management because it provided significant relative advantages over manual methods. Although the system was initially considered complicated, after training, officers were able to operate it well. The success of the system was also easily observed through increased inmate compliance with roll call rules and decreased incidents of violations. Keywords: Evaluation; Fingerprint System; Residential Room Roll Call; Sidoarjo Prison